2011
DOI: 10.1007/s11703-011-1062-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure, diversity, and regeneration potential of Monotheca buxifolia (Falc.) A. DC. dominated forests of Lower Dir District, Pakistan

Abstract: This study reports on the multivariate analysis of the vegetation of Hindukush Range in Pakistan, concentrating on the structure and regeneration potential of Monotheca buxifolia and associated tree species. Twenty stands at different locations in the Dir District of the Hindukush Range in Pakistan were chosen for the study. A point centered quarter method for trees and 5 m  5 m size quadrats were used for the sampling of understorey vegetation, including shrubs, seedlings, and saplings, respectively. The und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
8
26
1
Order By: Relevance
“…Several workers have emphasized the role of aspects on the specific vegetation distribution in different areas of Pakistan and even in the world. Khan et al (2011) reported that Monotheca buxifolia grow well on eastern aspects, Quercus baloot on the South-East (Khan, 2012) and Pinus roxburghii on Northern aspects (Siddiqui et al, 2009;Khan et al, 2014) with specific understory species in northern Pakistan. Somewhat similar findings were also reported by Shariatullah (2013) in Justicia shrub-land and most recently by Ali (2016) in Olea ferruginea dominated forests from Malakand division.…”
Section: Species Richness and Diversitymentioning
confidence: 99%
“…Several workers have emphasized the role of aspects on the specific vegetation distribution in different areas of Pakistan and even in the world. Khan et al (2011) reported that Monotheca buxifolia grow well on eastern aspects, Quercus baloot on the South-East (Khan, 2012) and Pinus roxburghii on Northern aspects (Siddiqui et al, 2009;Khan et al, 2014) with specific understory species in northern Pakistan. Somewhat similar findings were also reported by Shariatullah (2013) in Justicia shrub-land and most recently by Ali (2016) in Olea ferruginea dominated forests from Malakand division.…”
Section: Species Richness and Diversitymentioning
confidence: 99%
“…Most of the medicinal plants are currently found facing threat of extinction due to natural and Ecologically Pakistan is alienated into 9 regions having 6000 plant About 10 to 12 % of these are used for medicinal purposes [5]. According to Hocking (1985) 84% of Pakistani villagers are still practicing from practitioners of traditional drugs [16], either due to lack of proper health facilities of elders from several decades [18] in Pakistan with time as significant amount of work has been carried out in different parts of the country literature study confirms that previously no such work has carried out on the present study area. This precious kn transmitted from generation to generation verbally.…”
Section: Introductionmentioning
confidence: 99%
“…These forests have provided a wide variety of ecological and economic services to the local human populations over centuries (Khan et al, 2011). The species is known for its edible fruits with fleshy red, pink, or whitish external layers (Lama et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently distributed below the pine zone and is rarely found in association with Pinus roxburghii (personal observations). Monotheca buxifolia and Olea ferruginea are the most common and economically important species associated with Punica granatum forests (Khan et al, 2011) between 700 and 1800 m of altitude, whereas P. roxburghii grows between 700 and 2200 m above sea level and has no association with Punica.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation